An Analysis On English Teaching Techniques And Educational Values Found In “Freedom Writers” Movie - Miftahul Rizkon; Ari Prasetya Ningrum; Hajriana Arfah; Usuluddin (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to discover the teaching techniques and educational values in the Freedom Writers movie. The method used in this research is qualitative with a descriptive qualitative design. The data collection technique in this research is watching the movie, classifying and writing the teaching techniques and educational values found, and then coding the data. The data analysis techniques use a procedure by Cresswell. The result of this research shows that there are nine teaching techniques found in the movie: authentic material, transformation drill, task-based instruction, creative adaption, teacher silence, paragraph writing, guided writing, reading aloud, and journal writing. Moreover, nine educational values are found in this movie: honesty, courage, self-discipline, loyalty, respect, self-confidence, love and affection, kindness and friendliness, and justice.